Assessment of 1-D Channel Flow Models for Tritium Breeding Blanket Cooling - Gehrig, Monica L.; Humrickhouse, Paul W. (IEEE transactions on plasma science, 2024)
As the push for the design and construction of a fusion pilot plant in the U.S. continues, the demand for improved tools and techniques that aid this process increases. Reliable and rapid integrated simulations of neutronics, heat transfer, fluid flow, and other phenomena occurring in fusion reactors are necessary to aid in the efficient design of these complicated systems. Computational fluid dynamic (CFD) simulations can be a computationally expensive part of such simulations, and 1-D "thermal hydraulic" models can greatly reduce this expense; the use of integrated modeling frameworks such as the Multiphysics Object-Oriented Simulation Environment (MOOSE) can facilitate coupling of these simplified fluid models to fully detailed 3-D structures. Such a "hybrid fidelity" approach can accelerate the design process but requires suitable closures for friction and heat transfer in the 1-D fluid model. This work aims to evaluate the accuracy of such closures in the MOOSE thermal hydraulics module (THM) by comparing these directly to 3-D CFD models built using Simcenter STAR-CCM+. Channel geometries and conditions representative of the fusion nuclear science facility (FNSF) are considered, including those with radial/toroidal and poloidal orientations, and with bends. In both models, prototypic surface and volumetric heating conditions are applied to steady-state helium flows with ideal gas properties at 8 MPa. Quantities from the THM and CFD simulations, such as Nusselt number and limiting temperatures, are compared to each other, existing correlations, and literature in assessing the validity of the 1-D models.